Impact of periodontal disease on cognitive disorders, dementia, and depression: a systematic review and meta-analysis - Dibello, Vittorio; Custodero, Carlo; Cavalcanti, Raffaele; Lafornara, Domenico; Dibello, Antonio; Lozupone, Madia; Daniele, Antonio; Pilotto, Alberto; Panza, Francesco; Solfrizzi, Vincenzo (GeroScience, 2024)
A growing body of research suggested that there was a link between poor periodontal health and systemic diseases, particularly with the early development of cognitive disorders, dementia, and depression. This is especially true in cases of changes in diet, malnutrition, loss of muscular endurance, and abnormal systemic inflammatory response. Our study aimed to determine the extent of these associations to better target the multi-level healthy aging challenge investigating the impact of periodontal disease on cognitive disorders (cognitive impairment and cognitive decline), dementia, and depression. We conducted a comprehensive literature search up to November 2023 using six different electronic databases. Two independent researchers assessed the eligibility of 7363 records against the inclusion criteria and found only 46 records that met the requirements. The study is registered on PROSPERO (CRD42023485688). We generated random effects pooled estimates and 95% confidence intervals (CI) to evaluate whether periodontal disease increased the risk of the investigated outcomes. The quality assessment revealed moderate quality of evidence and risk of bias. Periodontal disease was found to be associated with both cognitive disorders (relative risk (RR) 1.25, 95% CI 1.11–1.40, in the analysis of cross-sectional studies); cognitive impairment (RR 3.01, 95% CI 1.52–5.95 for longitudinal studies, cognitive decline); and dementia (RR 1.22, 95% CI 1.10–1.36). However, no significant increased risk of depression among subjects with periodontal disease was found (RR 1.07, 95% CI 0.95–1.21). Despite the association with two of the three explored outcomes, the available evidence on periodontal diseases and dementia, cognitive disorders, and depression is controversial due to several limitations. Therefore, further investigations involving validated and standardized tools are required.